2017
DOI: 10.1016/j.jsp.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial examining the effects of Conjoint Behavioral Consultation in rural schools: Student outcomes and the mediating role of the teacher–parent relationship

Abstract: The results of a large-scale randomized controlled trial of Conjoint Behavioral Consultation (CBC) on student outcomes and teacher-parent relationships in rural schools are presented. CBC is an indirect service delivery model that addresses concerns shared by teachers and parents about students. In the present study, the intervention was aimed at promoting positive school-related social-behavioral skills and strengthening teacher-parent relationships in rural schools. Participants were 267 students in grades K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 76 publications
(63 reference statements)
3
122
0
Order By: Relevance
“…All other interviews were conducted in small groups with one teacher, parents of 2-3 children in their classroom, and a consultant. Source: Sheridan et al (2012). A randomized trial examining the effects of conjoint behavioral consultation and the mediating role of the parent-teacher relationship.…”
Section: Interview Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…All other interviews were conducted in small groups with one teacher, parents of 2-3 children in their classroom, and a consultant. Source: Sheridan et al (2012). A randomized trial examining the effects of conjoint behavioral consultation and the mediating role of the parent-teacher relationship.…”
Section: Interview Objectivesmentioning
confidence: 99%
“…Furthermore, parents who participate in the CBC process have reported more bi-directional communication with teachers and more positive, high quality relationships with their child's teacher (Sheridan, Clarke, Knoche, & Edwards, 2006;Sheridan et al, 2013). Importantly, the parent-teacher relationship has been found to be partially responsible as a mechanism of change that drives student success in urban settings (Kim, Sheridan, Kwon, & Koziol, 2013;Sheridan et al, 2012).…”
Section: Overview Of Conjoint Behavioral Consultationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since parent associations appear to have more influence in schools serving higher proportions of minority students, they may be able to advocate for reductions in the presence of exclusionary practices and the institution of more restorative approaches in schools serving greater percentages of these student groups. Indeed, recent work outlining a framework for reducing disparities in school discipline include family connections and input on policy as one component for successful disciplinary reform, a suggestion that is supported by research on the involvement of family in resolving disciplinary infractions (Gregory, Skiba, & Mediratta, 2017;Sheridan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To date, little research has been conducted exploring the pathways (i.e., mediators) by which these goals are achieved. (One notable exception is Sheridan et al [2012a], who identified the teacher-parent relationship as partially responsible for mediating the effects of CBC on social outcomes for students with behavioral concerns.) Figure 9.1 is presented as a theoretical model specifying the primary independent and dependent variables, potential mediators and moderators, and their hypothesized relationships within the CBC intervention.…”
Section: Active Ingredientsmentioning
confidence: 99%